Garbhagriha of the Shiva Temple (Temple 1) - Temples of India Project Team (Jio Institute, 2024)
At the centre of the garbhagriha (sanctum sanctorum) of the Shiva Temple (Temple 1) in Cluster 1 a Shiva linga, without the yonipatta (womb-shaped base of the linga), is placed. The floor is not flat and shows the dilapidated condition of the temple. Sometimes the devotees worship the linga.